Genetics and evolution of plumage color in Crested Ibis: Analysis of the melanocortin-1 receptor (MC1R) - Yang, J; Liu, X; Zhang, J; Qing, B; Lu, B (Cellular and Molecular Biology, 2015)
The melanocortin-1-recepter gene (MC1R), an important regulator in melanin synthesis, may cause different plumage color patterns in birds: gain-of- function mutations lead to the synthesis of eumelanin, whereas loss-of-function mutations help to generate pheomelanin synthesis. We had chosen MC1R as a candidate gene for the depigmentation of crested ibis, cloned and sequenced the crested ibis MC1R gene the first time. The crested ibis MC1R sequence, highly conserved with other birds during evolution, had seven transmembrane domains which played an indispensable function through evolution. We did not found any substitution on this sequence among all the sample individuals. The phylogenetic tree showed that crested ibis separated early in the evolution of birds. TYR, TYRP1, TYRP2 and MC1R were expressed in blood and the expression of the four genes showed no significant difference (p>0.05) between normal and albinism individuals, and this result demonstrated that melanic pigments are not involved in the production of red pigmentation in birds. Further study of the crested ibis albinism should focus on analyzing carotenoid-based genes.